'A Grandiose Time of Coexistence': Stratigraphy of the Anthropocene. Issue 4 (November 2016) - Colebrook, Claire
Abstract : Using Deleuze and Guattari's concept of stratigraphy, it is possible to open the question of the limits and range of the Anthropocene. Geological stratification has enabled a view of time and the earth that has opened new horizons, but this mode of stratification is one among others. Other stratifications are possible, not only those that would be compossible with the story of the Anthropocene (such as the histories of capital, empire and industrialism), but also incompossible stratifications, at odds with the history of man.